No evidence of disease activity (NEDA) analysis by epochs in patients with relapsing multiple sclerosis treated with ocrelizumab vs interferon beta-1a - Havrdová, Eva; Arnold, Douglas L; Bar-Or, Amit; Comi, Giancarlo; Hartung, Hans-Peter; Kappos, Ludwig; Lublin, Fred; Selmaj, Krzysztof; Traboulsee, Anthony; Belachew, Shibeshih; Bennett, Iain; Buffels, Regine; et al. (Multiple sclerosis journal - experimental, translational and clinical, 2018)
BACKGROUND: No evidence of disease activity (NEDA; defined as no 12-week confirmed disability progression, no protocol-defined relapses, no new/enlarging T2 lesions and no T1 gadolinium-enhancing lesions) using a fixed-study entry baseline is commonly used as a treatment outcome in multiple sclerosis (MS). OBJECTIVE: The objective of this paper is to assess the effect of ocrelizumab on NEDA using re-baselining analysis, and the predictive value of NEDA status. METHODS: NEDA was assessed in a modified intent-to-treat population (n = 1520) from the pooled OPERA I and OPERA II studies over various epochs in patients with relapsing MS receiving ocrelizumab (600 mg) or interferon beta-1a (IFN β-1a; 44 μg). RESULTS: NEDA was increased with ocrelizumab vs IFN β-1a over 96 weeks by 75% (p < 0.001), from Week 0‒24 by 33% (p < 0.001) and from Week 24‒96 by 72% (p < 0.001). Among patients with disease activity during Weeks 0‒24, 66.4% vs 24.3% achieved NEDA during Weeks 24‒96 in the ocrelizumab and IFN β-1a groups (relative increase: 177%; p < 0.001). CONCLUSION: Superior efficacy with ocrelizumab compared with IFN β-1a was consistently seen in maintaining NEDA status in all epochs evaluated. By contrast with IFN β-1a, the majority of patients with disease activity early in the study subsequently attained NEDA status with ocrelizumab.
Keywords: MRI activity; disability progression; relapse; NEDA; disease activity